Address of Shri K.C. Pant Deputy Chairman Planning Commission the National Development Council (49th Meeting) - Planning Commission (Planning Commission, 2001)
Let me begin by thanking the Prime Minister for his inspiring address and setting the tone for today’s deliberations. As he has pointed out, there has been progressive convergence in our ideological and conceptual positions on economic and social policies. We have to channelise this consensus into decisive action for the welfare of the people. The country expects this apex body to send a clear signal of our collective political will to pool our resources and energy for the greater good of the nation.
National Development Council
Planning Commission